MANAGEMENT OF ANTICOAGULATION IN ATRIAL FIBRILLATION: MINIMIZING DRUG INTERACTIONS WITH DOACS - da Silva, Sarah Camila Santos; Lee, Marcelo Simonelli; Dell'Antonia, Victor Tadeu; Martiniano, Felipe Santos Teixeira; da Luz, Elton Ramos; Fiore, Sérgio Augusto Peres; Morais, Pietro Conrado Carneiro Quadros; Veraldi, Priscylla Silva (ARACÊ, 2024)
Introduction: Atrial fibrillation (AF) is a common cardiac arrhythmia that elevates the risk of thromboembolic events, necessitating effective anticoagulation strategies. Direct oral anticoagulants (DOACs) have become the preferred choice due to their safety profiles; however, drug interactions can compromise their efficacy and safety. Objective: This study aims to assess the impact of drug interactions on the efficacy and safety of DOACs in patients with AF. Method: A literature review was conducted using databases such as the Virtual Health Library, LILACS Plus, and Medline, focusing on articles published from 2019 to 2024. Inclusion criteria emphasized studies related to drug interactions involving DOACs and AF, resulting in the selection of 13 relevant articles. Results: The analysis revealed a significant prevalence of drug interactions among patients treated with DOACs. Co-prescription with CYP3A4 inhibitors and P-glycoprotein modulators was linked to increased bleeding risks. Factors such as age, renal function, and the presence of comorbidities were crucial in determining appropriate dosing and the risk of adverse events. Conclusion: Careful management of AF patients on DOACs is vital to mitigate risks associated with drug interactions. Personalized treatment approaches that consider individual clinical profiles and ongoing education for healthcare providers are essential to optimize anticoagulation therapy.